Captive Labor: The 1849 Law and the Beginnings of Foreign Immigration in Republican Peru - Situ Chang, Miguel (2021)
Diverting from the liberal ideals that inspired independence, republican Peru maintained slave labor, which, combined with low wages, drove away natural-born workers from coastal agriculture. During the guano era, landowners sought to address the labor shortage by resorting to foreign immigration. In this context, under legislation enacted on November 17, 1849, Asian and European nationals migrated to a country that was not receptive to foreigners. Opponents of Chinese immigration in the 19th century labeled the law as «ley chinera» and attempted to stigmatize it as exclusively targeted to Chinese immigration. These attitudes have prevented a full understanding of the motives underlying the immigration policy of the time, as well as the persistence of slave labor imposed on unsuspecting foreign workers in Peru.